A Byrnes Family Ranch: A Good Day to Kill - Book 6 - Richards, Dusty (Waterville, Maine : Thorndike Press, A part of Gale, Cengage Learning, 2015)
When he expands the family ranch in the lawless Arizona Territory, Chet Byrnes, while trying to keep his empire safe from outlaws and Mexican military men, is caught in the middle of an all-out shooting war where only one man will be left standing.
Keywords: Large print books; Western fiction